The Impact of Taxation and Valuation Practices on the Timing and Efficiency of Land Use - Bentick, Brian L. (Journal of Political Economy, 1979)
[It is generally assumed that a tax on land ownership is always neutral toward resource allocation. Where land rentals change over time it is shown that the tax is neutral only where the tax base is current income as distinct from current market value. Taxes based on current market value are shown to favor investment projects with a short gestation period and to involve significant resource costs. These costs are considerably reduced if property appraisers, in assessing current market value, interpret the "highest and best use" of a property as that use which offers the greatest current income as opposed to its future income.]